2017
DOI: 10.1016/j.jrtpm.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A microscopic evaluation of railway timetable robustness and critical points

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The studied railway stretch is part of the Scandinavian-Mediterranean freight rail corridor, and connects continental Europe to Hallsberg, the largest marshalling yard in Scandinavia; substretches are, for example, considered in Khoshniyat and Peterson (2017) and Solinen et al (2017), and references therein.…”
Section: Experimental Study: Malmö-hallsbergmentioning
confidence: 99%
“…The studied railway stretch is part of the Scandinavian-Mediterranean freight rail corridor, and connects continental Europe to Hallsberg, the largest marshalling yard in Scandinavia; substretches are, for example, considered in Khoshniyat and Peterson (2017) and Solinen et al (2017), and references therein.…”
Section: Experimental Study: Malmö-hallsbergmentioning
confidence: 99%
“…Furthermore, in order to increase the robustness of timetable, Andersson et al [2] presented the robustness in critical points (RCP) to formulate a MILP model with the objective to add the time margins in the critical points while minimizing the deviation from the planned timetable. Solinen et al [12] presented the implementation of RCP and determined the impact of increased RCP value on the timetable performance. Abid et al [13] extended the concept of RCP to single-track train timetables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inequality (11) ensures that no train will start before the prespecified time at the origin. An activity cannot take more time than the duration of that activity that is applied by (12). Equation (13) puts the constraint on the minimum dwell times at the stations and (14) is to ensure the safe operations along the corridor by placing headways.…”
Section: ( )mentioning
confidence: 99%
“…In the adjusted case, total delays at the end station are 28% lower. Solinen et al [74] also use an optimisation model to increase the RCP throughout a timetable and evaluate the results with simulation. They found that robustness increased locally, but that the relationship between ex post measures and RCP must be studied further.…”
Section: Robust Timetablesmentioning
confidence: 99%